The Role of Career Development and Job Satisfaction in Reducing Turnover Intention in the Broadcasting Industry - Meisya Rahmatia Zefania; Mei Retno Adiwaty (International Journal of Economics and Management Sciences, 2025)
High turnover intention has become a critical issue in the broadcasting industry, especially in divisions that operate under fast-paced tasks and high levels of pressure. This study aims to analyze the influence of career development and job satisfaction on employees’ intention to leave the organization. Career development is measured through indicators such as promotion opportunities, work experience, and training, while job satisfaction is assessed through compensation, work environment, and recognition. A quantitative research design was applied, utilizing Partial Least Square (PLS) to analyze data obtained from a survey of employees working in a broadcasting company in Surabaya. The findings demonstrate that both career development and job satisfaction have a significant negative relationship with turnover intention, meaning that improvements in these variables can effectively reduce employees’ desire to quit. Among the career development indicators, work experience was found to be the most dominant factor influencing employee retention. On the other hand, recognition emerged as the most influential dimension of job satisfaction, showing that appreciation from the organization plays a crucial role in maintaining employee commitment. Overall, this study highlights the importance for broadcasting companies to implement effective career development strategies and enhance job satisfaction in order to minimize turnover intention and sustain organizational stability.